2022
DOI: 10.7759/cureus.28522
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bullying and Its Association With Health-Related Quality of Life Among Adolescents in Jazan: A Cross-Sectional Study

Abstract: Background and aim: Bullying is one of the most significant problems that has emerged across the world. It has negative effects on physical, psychological, and social health, especially among adolescents. No previous studies have been conducted in the Jazan region of Saudi Arabia to investigate the association between bullying and health-related quality of life (HRQOL). The study aimed to estimate the prevalence of bullying and its association with HRQOL among adolescents in Jazan.Methods: A cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…After screening the articles for relevance, 14 articles that met the inclusion criteria were included in the present review. [6][7][8][18][19][20][21][22][23][24][25][26][27][28] The information pertaining to the study design and setting, objectives addressed, and all relevant findings including prevalence and type of violence are tabulated in Table 2. The studies highlighted that violence from a perpetrator and victim perspectives has preceding relevant factors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…After screening the articles for relevance, 14 articles that met the inclusion criteria were included in the present review. [6][7][8][18][19][20][21][22][23][24][25][26][27][28] The information pertaining to the study design and setting, objectives addressed, and all relevant findings including prevalence and type of violence are tabulated in Table 2. The studies highlighted that violence from a perpetrator and victim perspectives has preceding relevant factors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation is that the females’ EI is higher than the males’ EI is [ 62 , 63 ]. Another explanation could be that the prevalence of bullying victimization is lower among females than it is among males [ 64 , 65 , 66 ]. Friendships are valued highly among adolescents, particularly among females [ 82 ], and as a result, females may be less likely to report bullying incidents perpetrated by a friend for fear of social rejection [ 83 ], which weakens the correlation between EI and school victimization among females.…”
Section: Discussionmentioning
confidence: 99%
“…Females exhibit EI at higher levels than males do [ 62 , 63 ]. Moreover, the prevalence of bullying victimization is lower among females than it is among males [ 64 , 65 , 66 ]. Thus, the association between EI and bullying victimization may differ across sex.…”
Section: Introductionmentioning
confidence: 99%
“…This finding contrasts with the previous studies since most researchers found moderate to high bullying perpetration. For instance, the study of Elmahdy et al (2022) has shown that bullying is higher among adolescents in the Jazan region while Farrell & Vaillancourt (2020) revealed that a small number of adolescents have moderate level of bullying perpetration. In fact, AlBuhairan et al ( 2016) also reported that 26% of 9073 adolescents in their study have experienced bullying in a span of 30 days.…”
Section: Discussion Of Findingsmentioning
confidence: 99%